Differences in Values of Volume of Unedged Sawn Boards as a Result of Different Width Measurement Methods - Andreja Čunčić Zorić (University of Zagreb, Faculty of Forestry and Wood Technology, 2014)
The paper discusses various methods of measuring the width of unedged sawn boards with nominal thickness of 50, 60 and 80 mm, as well as the importance of measuring methods for the calculation of their volume. The starting point in determining the method of measuring the width of the boards were Croatian and European regulations as well as common methods of measuring used in Croatian sawmills. Experimental measurements were performed in a sawmill in Croatia. Based on the research results, it was concluded that there is a difference in the calculation of the volume of the unedged sawn boards as a result of the different methods used to calculate their width. For 50 mm thick sawn boards, the highest values of the measured volume were obtained by applying a measurement method common in Croatian sawmills, labelled as P2. This was followed by measurement methods according to HRN2, EN, and another method used in Croatian sawmills, labelled as P1, and finally by the HRN1 method; however differences in this case were not statistically significant. The EN method of measuring the width of sawn boards of 60 and 80 mm thickness resulted in the highest value of volume, followed by the HRN2 method, and finally methods used in the sawmills labelled as P2, P1 and HRN1; however differences were statistically signifi cant only with 80 mm sawn boards. For all the observed widths, measurement methods according to EN, HRN2 and the sawmill method, labelled as P2, resulted in smaller mutual deviations. With an increase of thickness, an apparent increase in volume was observed; however it was statistically signifi cant only for the planks with a thickness of 80 mm.